2023
DOI: 10.1002/jso.27258
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of dermatofibrosarcoma protuberans

Abstract: Dermatofibrosarcoma protuberans (DFSP) is an uncommon, locally aggressive cutaneous malignancy. Complete resection is the primary treatment but there is debate over the optimal method. Wide local excision was traditionally the standard of care; however, National Comprehensive Cancer Network guidelines now recommend Mohs micrographic surgery as the preferred approach. Medical therapy with imatinib can be used in advanced or unresectable disease. This review will discuss the current management of DFSP, focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In 2015, the European consensus suggested follow-up every 6 months for the first 5 years, followed by annual follow-up for the next 5 years, totaling 10 years of follow-up. Recurrent DFSP and DFSP with fibrosarcomatous transformation should undergo imaging examinations during follow-up, especially for DFSP with fibrosarcomatous transformation, as lung metastasis commonly occurs and routine lung monitoring is recommended [ 24 , 30 ]. Studies have shown that the median time from surgical excision to local recurrence is 32–38 months.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the European consensus suggested follow-up every 6 months for the first 5 years, followed by annual follow-up for the next 5 years, totaling 10 years of follow-up. Recurrent DFSP and DFSP with fibrosarcomatous transformation should undergo imaging examinations during follow-up, especially for DFSP with fibrosarcomatous transformation, as lung metastasis commonly occurs and routine lung monitoring is recommended [ 24 , 30 ]. Studies have shown that the median time from surgical excision to local recurrence is 32–38 months.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported that tumor size and the presence of metastasis at diagnosis were significant factors associated with worse outcomes. Finally, Rust et al reported that wide local excision with clear margins is an effective treatment approach for dermatofibrosarcoma protuberans, leading to low rates of recurrence and good long-term outcomes 58 . The study also explored the use of Mohs micrographic surgery and found it to be an appropriate treatment option for selected cases of dermatofibrosarcoma protuberans.…”
Section: Unique Soft-tissue Sarcoma Subtypesmentioning
confidence: 99%